(untitled) (MATEMATIKA, 2003)
Dalam makalah ini dipaparkan pembinaan homeomorfisma dari sfera berunit satu; S^2 ke elipsoid berunit satu pada satah-xy serta berkutub di z=2 dan z=-2; E^2 melalui struktur permukaan Riemann. Pembuktian secara pembinaan dan percanggahan diketengahkan. Katakunci: Permukaan Riemann; homeomorfisma In this paper, we present the construction of homeomorphism from unit sphere; S^2 to ellipsoid which is one unit in xy-axis and its poles are at z=2 and z=-2; E^2 through Riemann surface structures. Proving techniques by construction and contradiction are highlighted. Keywords: Riemann surface; homeomorphism